Outcome of very low birth weight (VLBW) babies born after attempted criminal abortion - Khuwutyakorn, Varangthip; Kosarat, Shanika (Biomedical Sciences and Clinical Medicine, 2024)
Objective To determine the mortality and short-term morbidities of very low birth weight (VLBW) babies who were born after attempted abortion. Material and method A retrospective study was done by reviewing charts of VLBW babies admitted to Chiang Mai University Hospital within 24 hours of age from January 2004 to December 2007. The mortality rate and morbidities were compared between VLBW babies born after attempted abortion and those in control group. Results Two hundred and twenty two VLBW babies were admitted in the NICU, twenty-fi ve (11.2%) babies were born after attempted abortion. The mothers in abortion group were younger (21.1±3.2 yrs vs. 27.9±6.7 yrs, p <0.05), had less prenatal care (4.0% vs. 91.8%, p <0.05). Less of them received antenatal steroid (32.0% vs. 58.8%, p 0.038). The mortality rates at 24 hours (4.0% vs. 4.1%, p 0.732), 7 days (16% vs. 10.7%, p 0.304), 28 days (20% vs. 13.2%, p 0.257) and at discharge (20% vs. 14.7%, p 0.33) were not significantly different between two groups. The incidence of respiratory distress syndrome; RDS (92% vs. 65%, p 0.03, RR 1.41 95%CI 1.21-1.65), necrotizing enterocolitis; NEC (36% vs.15.2%, p 0.015, RR 2.36 95% CI 1.27-4.39) and sepsis (40% vs. 21.8%, p 0.044, RR1.83, 95% CI 1.06-3.17) were higher in abortion group. Babies in abortion group received breast milk less than those in control group at 7 days (47.1% vs. 64.8%, p0.002) and 24 hours before discharge. (22.7% vs. 64.7%, p 0.001) Conclusion The mortality rate of VLBW babies who were born after attempted abortion was not different from control group. However, they had higher incidence of RDS, NEC and sepsis.